2018
DOI: 10.1021/jacs.8b03584
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Extracellular Vesicle-like Metal–Organic Framework Nanoparticles for Protection and Intracellular Delivery of Biofunctional Proteins

Abstract: The intracellular delivery of biofunctional enzymes or therapeutic proteins through systemic administration is of great importance in therapeutic intervention of various diseases. However, current strategies face substantial challenges owing to various biological barriers, including susceptibility to protein degradation and denaturation, poor cellular uptake, and low transduction efficiency into the cytosol. Here, we developed a biomimetic nanoparticle platform for systemic and intracellular delivery of protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
273
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(277 citation statements)
references
References 57 publications
4
273
0
Order By: Relevance
“…[10,11,56,57] Furthermore,i ncreasing efforts were devoted to construct biomacromolecule@nanoZIF-8 intracellular delivery systems for protein-and gene-based theranostics. [25,[58][59][60] These applications receive more and more attention because of the high loading efficiency and protecting effect of ZIF-8, and the convenient de novo synthesis process.H erein, we highlighted the importance of the embedding patterns for facilitating and preserving the biofunctionality of abiomacromolecule encapsulated within ZIF-8. Importantly,o ur work demonstrated that the embedding patterns can be controlled by chemical modification of the amino acids of the protein that enabled the modulation of the biofunctionality of proteins@ZIF-8.…”
Section: Resultsmentioning
confidence: 99%
“…[10,11,56,57] Furthermore,i ncreasing efforts were devoted to construct biomacromolecule@nanoZIF-8 intracellular delivery systems for protein-and gene-based theranostics. [25,[58][59][60] These applications receive more and more attention because of the high loading efficiency and protecting effect of ZIF-8, and the convenient de novo synthesis process.H erein, we highlighted the importance of the embedding patterns for facilitating and preserving the biofunctionality of abiomacromolecule encapsulated within ZIF-8. Importantly,o ur work demonstrated that the embedding patterns can be controlled by chemical modification of the amino acids of the protein that enabled the modulation of the biofunctionality of proteins@ZIF-8.…”
Section: Resultsmentioning
confidence: 99%
“…(F) Poly(3,4-ethylenedioxythiophene) (PEDOT) infusion into leaves by a syringe (48). (G) Schematic illustration of the biomimetic EV-MOF protein nanoparticles and the intracellular delivery of proteins (78). (H) Schematic illustration of biomimetic crystallization of cytoprotective MOF coatings on living yeast cells (11).…”
Section: Exogenous Bioaugmentationmentioning
confidence: 99%
“…(K) Illustration of MOF formation inside of living plants (15). Reproduced with permissions from the Royal Society of Chemistry (22), American Chemical Society (78,86) Springer Nature (39), Wiley-VCH (11,15,44,62), National Academy of Sciences (80), and American Association for the Advancement of Science (48).…”
Section: Exogenous Bioaugmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrides of Eu 3+ and GMP dissociated under acidic conditions, which accelerated protein escape from endosomal and lysosomal compartments to enhance antigen cross‐presentation and thus CTL stimulation. Zheng and co‐workers developed a MOF‐based nanocarrier decorated with extracellular vesicle membranes . The authors encapsulated protein (gelonin) into MOF (ZIF‐8) matrices with high loading efficiencies and coated the MOF particles with extracellular vesicle membranes, preventing protein degradation by proteases and enabling significant inhibition of tumor growth.…”
Section: Nanoscale Materials For Immunotherapymentioning
confidence: 99%